PENDIDIKAN AGAMA ISLAM DAN EKONOMI: SEBUAH ANALISIS KONSEPTUAL - Latifah, Eny; Mahfudoh, Sitti Atiyatul; Yusuf, Yusuf (Jurnal Multidisipliner Bharasumba, 2026)
This article aims to examine and identify the concept of economic values embedded in Islamic Religious Education and to analyze how Islamic values can be integrated into the economic behavior of individuals and society. A conceptual analysis method is employed to understand the relationship between Islamic Religious Education and economic activities in social life. The findings indicate that education grounded in Islamic teachings plays a significant role in shaping ethical, responsible, and equitable economic behavior, while also increasing awareness of the importance of applying Islamic values in economic practices. However, the integration of Islamic Religious Education and economics still faces several challenges, particularly related to limited resources, inadequate infrastructure, and the lack of an integrated curriculum. Therefore, it is necessary to develop a more holistic and integrated curriculum that combines Islamic Religious Education and economic principles to support the formation of sustainable economic behavior based on Islamic values.